Case of death in a child with generalized HIV-infection and PCP - V. E. Karev; N. V. Skripchenko; A. V. Vakhnina (Журнал инфектологии)
The article presents a case of death of the young child, carries generalized HIV complicated by Pneumocystis pneumonia. Clinic HIV encephalitis so scarce that the disease is difficult to diagnose and manifestation of symptoms of HIV infection may begin with opportunistic infections, as in the present clinical observation.